Singaporean Demand For Tourism In Malaysia - Puah, Chin Hong; Thien, Fung Thai; Mohammad Affendy, Arip (Institute of Society Transformation, 2014)
Tourism is among the most important service industries in Malaysia. It plays a crucial role in the new economic model, in which the government is increasing its efforts to shift the border of economic activities from a resource-based to a service -based economy. One of Malaysia’s major tourist origination countries is Singapore, which accounts for more than half of the annual to urist arrivals in Malaysia. Looking at the significant volume of tourist arrivals from Singapore, this paper investigated the determi nants of Singaporean tourism demand in Malaysia from a macroeconomic perspective using quarterly data from 2000Q1 through 2010Q4. The empirical results suggest a long-term cointegration relationship between Singaporean tourist arrivals and specified macroec o- nomic variables, including real Singaporean income, tourism price, real travel cost, and currency exchange rate between Singapo re and Malaysia. In particular, higher real income and stronger currency will induce Singaporeans to visit Malaysia, while higher tourism prices and travel costs will discourage tourists from Singapore. It is difficult to infer specific policy for the touri sm industry using foreign real income and exchange rates, h owever, a deta iled microeconomic survey on tourist demand behavior regarding tourism prices and travel costs should be conducted and addressed by the Malaysian tourism action plan.